Synthesis, Characterization and Photovoltaic Properties of Electron‐Accepting (11‐Oxoanthra[2, 1‐b]thiophen‐6‐ylidene)dipropanedinitrile‐Based Molecules. Issue 24 (29th June 2021) - Baranov, Denis S.; Nevostruev, Danil A.; Kazantsev, Maxim S.; Zinoviev, Vladimir A.; Zelentsova, Ekaterina A.; Dmitriev, Alexey A.; Gritsan, Nina P.; Tsentalovich, Yuri P.; Kotova, Maria; Düreth, Johannes; Sperlich, Andreas; Dyakonov, Vladimir; et al.
Abstract: Two acceptor small molecules consisting of 2‐(11‐oxoanthra[2, 1‐ b ]thiophen‐6‐ylidene)dipropanedinitrile frameworks connected by a bis(thiophen‐2‐ylethynyl)arene bridge were synthesized by the two‐step sequence of Sonogashira cross‐coupling and Knoevenagel condensation in order to investigate their performance as non‐fullerene acceptors in organic solar cells. Optical, electrochemical and photovoltaic properties of new 2, 2′‐[2, 2′‐(5, 5′‐(arenediyl)bis(ethyne‐2, 1‐diyl)bis(thien‐5, 2‐diyl))bis(11‐oxoanthra[2, 1‐ b ]thiophen‐6‐ylidene)]dipropanedinitriles and previously studied analogs of 2, 2′‐[2, 2′‐arenediylbis(11‐oxoanthra[1, 2‐ b ]thiophene‐6‐ylidene)]dipropanedinitriles were compared to assess the effect of introducing ethynylthiophene units between the arene linker and the 2‐(11‐oxoanthrathiophen‐6‐ylidene)propanedinitrile units. Despite the proper energy level alignment and morphology, composites of the newly synthesized compounds with the PBDB‐T donor polymer demonstrate a moderate PCE of 0.54 %. The small value of the short circuit current as compared to composites with fullerene acceptors is probably due to the low electron mobility in the newly synthesized compounds. The low electron mobility, in turn, is probably cause by the LUMO localization at the edge units of the acceptor‐type molecules, in contrast to the almost uniform LUMO delocalization over the whole π‐conjugated system for high‐performing non‐fullerene acceptors such as ITIC. Abstract : Anthrathiophene frameworks were used to create non‐fullerene acceptors for organic solar cells. Two anthrathiophene‐like molecules were synthesized. Morphology and photovoltaic properties of their composites with donor polymer PBDB‐T were investigated. The best‐performance device has PCE of 0.54 %. DFT calculations revealed non‐planar structure of anthrathiophene units, which is suggested to decrease electron mobility and to spoil OPV performance.